The relationship between spiritual well-being and psychological distress among Muslims throughout COVID-19 - Mohd Noor, Nurul Syazwani; Muhammad, Hamizah; Arifin, Juliana; Ismail, Che Zuina (Intelektual Pustaka Media Utama, 2023)
This is a conceptual paper of an ensuing study based on the literature review related to COVID-19 impact, spiritual well-being, and psychological distress. The impact of COVID-19 becomes more serious for those who face challenges in maintaining the stability of their lives financially and emotionally. It has become increasingly difficult for Muslims to worship in mosques during the previous movement control order (MCO) period. Academic research has less explored the impact of COVID-19 on the human lives in the context of the relationship between well-being status and psychological impact Thus, this study aims to assess for coming examination whether spiritual well-being have significant relationship with psychological distress among Muslims in Terengganu, Malaysia. The paper went through analyzing the issues and concepts for the further research through several multidisciplinary literatures. The result of the study thus proposed conceptual framework and relevant propositions to be tested in the next study. This conceptual study means adding to the literature for researchers as a reference for their study. It also pertinent to policymakers who mapping mental health support mechanisms and schemes as well as non-government organizations (NGOs) to promote the healthy lifestyle for people as whole.